Early Warning/Track-and-Trigger Systems to Detect Deterioration and Improve Outcomes in Hospitalized Patients - Shiloh, Ariel L.; Lominadze, George; Gong, Michelle N.; Savel, Richard H. (Seminars in Respiratory and Critical Care Medicine, 2016)
As a global effort toward improving patient safety, a specific area of focus has been the early recognition and rapid intervention in deteriorating ward patients. This focus on “failure to rescue” has led to the construction of early warning/track-and-trigger systems. In this review article, we present a description of the data behind the creation and implementation of such systems, including multiple algorithms and strategies for deployment. Additionally, the strengths and weaknesses of the various systems and their evaluation in the literature are emphasized. Despite the limitations of the current literature, the potential benefit of these early warning/track-and-trigger systems to improve patient outcomes remains significant.
Keywords: early warning/track-and-trigger systems; patient safety; patient deterioration; early detection; early response